Praat-Based Analysis Of Phonological Patterns In Pitch, Intensity And Duration Of Students’ News Reading At SMAN 1 Semaka - Shanti Anggraeni; Susanto Susanto; Deri Sis Nanda (International Journal of Education, Vocational and Social Science, 2024)
The aim of this research is to measure the pitch, intensity and duration of news reading by SMAN 1 SEMAKA students who take part in the English language club. In this study, we used PRAAT software to measure and analyze pitch, intensity, and duration. This research uses qualitative methods and analytical data collection tools to identify, with a sample size of 10 students with 50 news stories, so that each student reads 5 news stories. This analysis shows the results of measuring the pitch, intensity, and duration of each student at SMAN 1 SEMAKA, so this research also shows different measurement results of each individual student in reading the news which is measured by the length of each sentence.